(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the concept of syllable structure in English, highlighting its components, rules, and variations. A syllable, a fundamental unit of spoken language, forms the building blocks of words and has a significant impact on pronunciation, phonology, and linguistic analysis. This discussion delves into the anatomy of syllables, syllabification rules, and their implications for understanding English phonetics and phonology.This article provides a comprehensive overview of English syllable structure, offering insights into its components, classification, and rules. It emphasizes the practical implications for linguistics, language learning, and phonetics. Key challenges, such as non-correspondence between spelling and pronunciation, are also discussed to highlight the complexity of the English syllable system.